Iron metabolism patterns in non-anemic patients with myasthenia gravis: A cross-sectional and follow-up study - Li, Ke; Hou, Li'an; Tan, Ying; Huang, Yangyu; Shi, Jiayu; Han, Jianhua; Yan, Jingwen; Guan, Yuzhou (Frontiers in Neurology, 2022)
Background and purpose Iron metabolism in myasthenia gravis (MG) and factors associated with it are explored by few published studies. Therefore, this study aimed to compare iron metabolism patterns between patients with MG and healthy individuals as well as between the same group of patients before and after immunotherapy, and to identify predictors of iron metabolism disorders in MG. Materials and methods For this study, 105 patients and healthy individuals were included at baseline, after which paired parametric and non-parametric tests were adopted to compare their iron metabolism patterns, and multivariate binary logistic regression was used to identify predictors of iron metabolism disorders. Patients with MG were then followed up for 12 ± 3 months to explore alterations in their iron metabolism patterns after starting immunotherapy with the help of paired tests. Results Non-anemic immunotherapy-naive patients with MG had significantly lower serum iron (SI) and transferrin saturation (TS) levels than healthy individuals. Premenopausal female was significantly associated with SI < 65 μg/dL and iron deficiency in these patients. However, iron metabolism parameters did not significantly alter after around 12 months of immunotherapy in patients with MG. Conclusion Iron inadequacy was present in patients with MG, particularly premenopausal female patients, and it would hardly improve after immunotherapy. Given the significant role of iron in human body, it should be given more attention in patients with MG.